The effect of endorsement appeals in advertisement on food buyers’ purchase intention / Wan Nazriah Wan Nawawi ... [et al.] - Wan Nawawi, Wan Nazriah; Ramli, Noorazlin; Anuar, Jazira; Mohd Kamal, Malina Hanum; Adzmy, Azahar (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
Advertising is one of the modes of communication that influences the actions of the targeted market. It is crucial that companies understand the marketing communication tools that best suit their target customers. This study aims to determine the influence of endorsement appeals in advertising on the purchasing intention of Malaysia’s food buyers. A quantitative study was conducted on 385 respondents, and Likert-scale survey questionnaires were used to collect the data. Resultantly, attributes such as expertise, trustworthiness, attractiveness, and credibility of endorsement appeals influenced the purchase intention of food buyers in Malaysia. In the present sad and anxiety-driven world, delivering emotional and relatable feelings and conveying messages in an understanding and familiar manner is gaining popularity and mental acceptance among Malaysians. These findings support an underlying conviction that endorsement appeals could influence the purchase intention of food buyers. Apart from watching and enjoying the advertisement, the content also created an emotional advertising appeal, which helped to attract buyers. Surprisingly, the viewers preferred buying the same product or service as a form of achievement which resultedfrom the emotional advertising appeal. This proves that the marketers prefer the emotional advertising appeal to the rational advertising appeal. Conclusively, this study broadens the knowledge of assessments and impacts of emotional and logical appeals appearing either in print or online advertisements